Genome-wide approaches to studying chromatin modifications - Schones, Dustin E.; Zhao, Keji (Nature reviews. Genetics, 2008)
Key Points Chromatin modifications have been shown to have a profound impact on the regulation of gene expression. Epigenomes consist of the ensemble of all chromatin modifications in any given cell type, including DNA methylation, post-translational histone modifications, nucleosome positioning, histone variants, noncoding RNAs and three-dimensional chromatin architecture. New technologies, which allow for the profiling of chromatin modifications on a genome-wide scale, are providing researchers with comprehensive views of epigenomes. Genome-scale data sets for epigenetic phenomena allow for the use of bioinformatic methods to study epigenetics. Different functional regions of the genome are associated with distinct patterns of histone modifications and these patterns, in turn, can be used to annotate the functional elements in the genome. In multicellular organisms, the identity of a cell is determined by its unique gene expression pattern, which is remembered and passed on to daughter cells by epigenetic mechanisms. Recent technical advances are enabling researchers to look at how epigenetic changes are coordinated on a genome-wide scale, thus giving rise to a new field of epigenomics. Over two metres of DNA is packaged into each nucleus in the human body in a manner that still allows for gene regulation. This remarkable feat is accomplished by the wrapping of DNA around histone proteins in repeating units of nucleosomes to form a structure known as chromatin. This chromatin structure is subject to various modifications that have profound influences on gene expression. Recently developed techniques to study chromatin modifications at a genome-wide scale are now allowing researchers to probe the complex components that make up epigenomes. Here we review genome-wide approaches to studying epigenomic structure and the exciting findings that have been obtained using these technologies.